Use of instant messaging in electrophysiological clinical practice in Latin America: a LAHRS survey. Issue 1 (21st June 2022) - de Oliveira Figueiredo, Márcio Jansen; Cuesta, Alejandro; Duncker, David; Boveda, Serge; Guerra, Federico; Márquez, Manlio F
Abstract: Aims: Instant messaging (IM) platforms are a prominent component of telemedicine and a practical tool for sharing clinical data and counselling. Purpose of the survey was to inquire about the use of IM, the platforms used, frequency, recipients, and contents in Latin America region. Methods and results: An online survey was sent to medical community via newsletter and social media channels. The survey consisted in 22 questions, in Spanish and Portuguese, collected on SurveyMonkey. A total of 125 responders from 13 Latin-American countries (79% male, mean age 46.1 ± 9.7 years) completed the survey. Most of the responders declared that they send (88.8%) and receive (97.6%) clinical data through IM apps. Most senders declare that they anonymize clinical data before sending (71.0 ± 38.3%), but that the data received is anonymized only in 51.4 ± 33.5%. The most common tests shared with other physicians were 12-lead electrocardiograms (99.2%), followed by Holter recordings (68.0%) and tracings from electrophysiological studies (63.2%). The majority (55.2%) said that are unaware of legal data protection rules in their countries. Conclusions: IM apps are used by medical professionals worldwide to share and discuss clinical data and are preferred to many other methods of data sharing and are often used to share many different types of clinical data. They are perceived as a fast and easy way of communication, but medical professionals should be aware of the appropriate use of IM to prevent legal and privacy issues.